Educational for Technical Personnel of Krembangan Health Center in order to increase Awareness on Leakage Current Measurement for Medical Equipment and Patient Safety - Ridha Makruf, Muhammad; Priyambada Cahya Nugraha; Pudji, Andjar (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
The electrical safety of medical equipment is crucial to prevent hazards that endanger both healthcare workers and patients. Krembangan Health Center faces significant challenges due to staff's limited knowledge about electrical safety, including leakage current detection. The aim of this study was to enhance staff skills in ensuring electrical safety through a focused training program. The program covered the basics of electrical safety, leakage current risks, and practical use of a digital multimeter for inspections. Field surveys and practical training were conducted to inspect and measure electrical systems across the health center. Results revealed inadequate grounding, uneven load distribution, and leakage voltage up to 99 volts AC in the new building, while the old building had minor leakage issues. The conclusion emphasized the need for regular maintenance, comprehensive electrical safety audits, and ongoing staff training to ensure long-term safety. These efforts aim to create a safer healthcare environment, improving the reliability of medical equipment and safeguarding patient care.